A generic level review of Eupithecia Curtis and some closely related genera based on the Palaearctic, Nearctic and Oriental fauna (Lepidoptera, Geometridae, Larentiinae) - Mironov, Vladimir G.; Galsworthy, Anthony C. (Zootaxa, 2012)
The history of the genus Eupithecia Curtis is reviewed, and a preliminary redescription of the genus is proposed on the basis of the Palaearctic, Nearctic and Oriental fauna. Several Asian species previously placed in Eupithecia  have been found to be anomalous. These are examined and some are placed in related genera, two of them new (Pareupithecia and Girida). A further group (the ‘subrubescens’ group) is retained within Eupithecia as a separate species group. The genus Eva Vojnits is redescribed. A new species is described in the genus Mesoptila Meyrick. Descriptions are given of all genera involved, and full lists of taxa included within them, with the exception of Eupithecia itself. Selected adults and genitalia are illustrated. Taxonomic changes proposed in this paper include: new genera Pareupithecia, Girida; new species  Mesoptila murcida; new synonymies, Emmesocoma Warren, 1907 of Mesoptila Meyrick, 1891 and Horisme sternecki Prout, 1938 of Chloroclystis chingana Wehrli, 1926; new combinations Mesoptila melanolopha Swinhoe, 1895, Mesoptila unitaeniata Warren, 1906, Mesoptila deviridata Warren, 1907, Mesoptila excita Prout, 1958, Mesoptila festiva Prout, 1916, Eupithecia eurytera Prout, 1938, Eupithecia chingana Wehrli, 1926, Pareupithecia spadix Inoue, 1955, Girida rigida Swinhoe, 1892, Girida sporadica Prout, 1932; reinstated taxon Eupithecia brevifasciaria Leech, 1897; and status change  Girida sporadica Prout, 1932.